The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2190/de.40.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Speeding through the Frat House: A Qualitative Exploration of Nonmedical Adhd Stimulant Use in Fraternities

Abstract: Qualitative methods were used to investigate the use of nonmedical Attention Deficit Hyperactivity Disorder (ADHD) stimulants by fraternity members. The primary goal of the study was to determine students' levels of understanding and motivations for use of these Schedule II controlled substances. Seventy-nine in-depth interviews were conducted. Key findings highlighted how: a) easy it was for subjects to obtain stimulants; b) little health information nonmedical users have about stimulants; c) academic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 20 publications
2
71
0
Order By: Relevance
“…Using a revised coping model by Cooper et al (2008), we found that dysfunctional coping was related to CE use; however, this is unlikely to be the only factor related to students' enhancement practices. Previous studies have emphasized illicit drug use McCabe et al 2005;Schelle et al 2015); availability and association to other CE users (Desantis et al 2010;Vrecko 2015); and attitudes (Partridge et al 2012) as important drivers. It will therefore be important for future research to both replicate our main finding and to further explore the relationship between coping styles and the range of other factors known to impact CE use.…”
Section: Discussionmentioning
confidence: 99%
“…Using a revised coping model by Cooper et al (2008), we found that dysfunctional coping was related to CE use; however, this is unlikely to be the only factor related to students' enhancement practices. Previous studies have emphasized illicit drug use McCabe et al 2005;Schelle et al 2015); availability and association to other CE users (Desantis et al 2010;Vrecko 2015); and attitudes (Partridge et al 2012) as important drivers. It will therefore be important for future research to both replicate our main finding and to further explore the relationship between coping styles and the range of other factors known to impact CE use.…”
Section: Discussionmentioning
confidence: 99%
“…The non-medical use or misuse of stimulants, usually defined as taking stimulants without a valid prescription or greater use of stimulants than as prescribed (Benson et al, 2015;Weyandt et al, 2013b), has soared among university students since the beginning of the century (Babcock & Byrne, 2000;DeSantis, Noar, & Webb, 2010;DuPont, Coleman, Bucher, & Wilford, 2008;Dussault & Weyandt, 2013;Hall, Irwin, Bowman, Frankenberger, & Jewett, 2005;Janusis & Weyandt, 2010;Judson & Langdon, 2009;Low & Gendaszek, 2002;Messina et al, 2014;McCabe et al, 2005;McCabe, West, Teter, & Boyd, 2014;Rabiner et al, 2009;Sharp & Rosen, 2007;Verdi, Weyandt, & Zavras, 2014;Weyandt et al, 2009;White, Becker-Blease & Grace-Bishop, 2006 A systematic review of the literature conducted by Weyandt and colleagues (2013) revealed that several reasons for misusing prescription stimulants have been reported, chief among them being cognitive and academic enhancement. More specifically, college students who disclose engaging in stimulant misuse report doing so while studying (e.g., preparing for exams, writing papers) to increase their attention and alertness, and thus improve their academic performance.…”
Section: Use and Misuse Of Prescription Stimulantsmentioning
confidence: 99%
“…Jocks may be susceptible to the dangers of energy drink consumption whereas athletes may not be. In addition, future research should examine the differences between "high-risk" and "low-risk" fraternities (DeSantis, Noar, & Webb, 2010) and how the two groups differ in terms of energy drink consumption and the requisite problems associated with energy drinks. In brief, "low-risk" fraternities are more inclusive and respectful whereas "high-risk" fraternities possess more traditional and monolithic attitudes toward masculinity, alcohol, sexual coercion, and so forth.…”
Section: Limitations and Future Directions For Researchmentioning
confidence: 99%